The Appearance of Expressiveness in Media Language (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article talks about the subjective attitude to the text of information transmission in the context of the expressiveness of the text of information transmission, the quality of speech that ensures the completeness of the text - the analysis of language that increases the effectiveness, pay attention to the trends of expressiveness.